Can corporate social responsibility (CSR) be recruited? : an insight to future employees' values and perceptions on attractive employers - Honkala, Henna (2013)
Many businesses acknowledge that they want to achieve the best possible employees in order to succeed in the markets in the near future. This study takes a stance on who these employees, the future talents, are and what do they value, especially from the Corporate Social Responsibility (CSR) point of view. Thus future employees’ values and their aspirations towards attractive employers are observed in this qualitative, theme-interview based study conducted to Master’s level students of University of Jyväskylä, School of Business and Economics. The results show that there are five (5) different classes of future employees, which are Environmental Idealists, Equality Enhancers, Corporate Money-Makers, Aware Sceptics and Safety Seekers, whose values and demands regarding their future employers vary from class to another. The study gives thus both theoretical and practical implications on how these values and demands can be adjusted to corporate recruitment and CSR strategies and, consequently, how the organisations can tempt the best, future talents to their organisations. To summarise, the organisations should assure the value congruence between the prospective employee and the organisation in order to gain multiple benefits from competitive advantage to employee commitment and motivation as well as to build solid, trustworthy and successful CSR programmes that involve employees from all levels of the organisation in order to create, maintain and execute the goals set. Due to the quite evident generational shift happening in the workplaces in the near future, employers should take the values, needs and demands of their future employees with serious regard in order to both attract them to work for them but increasingly also because CSR is a relevant tool to assure the continuity of business actions also in the years to come.